High schoolers’ views on academic integrity. - Bacha, Nahla Nola (2012)
The issue of academic integrity in cheating on exams and plagiarising in writing is not a new one. All schools need to address this problem and some more than others. In the L2 context, the issues become more complex as non‐native students need to adhere to the ‘culture of learning’ of a Western model of academic integrity if they are to be accepted and succeed in higher education Western communities. Unfortunately, no research has been carried out in the Lebanese contexts as to the scope of the problem and how these issues are being dealt with at the pre‐university level. This exploratory study surveys 3986 high school students attending Grades 10–12 on their views of the extent of student cheating and plagiarism. It also examines any significant differences among the student grade levels. Recommendations are made for activities to raise students’ awareness of academic integrity according to Western practices and for future needed research.